2020
DOI: 10.21873/invivo.12090
|View full text |Cite
|
Sign up to set email alerts
|

The Short- and Long-term Outcomes of Gastrectomy in Elderly Patients With Gastric Cancer

Abstract: Background: The short-and long-term outcomes of gastrectomy in elderly patients with gastric cancer have not been fully evaluated. Patients and Methods: Patients who underwent gastrectomy were classified into two groups: Nonelderly patients (<80 years old) and elderly patients (≥80 years old). The surgical morbidity, overall and cancerspecific survival in the two groups were compared. Results: A total of 411 patients were evaluated. The rate of overall complication was 29.4% in the non-elderly and 32.4% in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
(9 reference statements)
1
4
0
1
Order By: Relevance
“…Studies have consistently shown that postoperative complications are associated with decreased long-term survival and increased long-term morbidity [ 34 39 ]. Our findings align with research suggesting that comprehensive preoperative supports can lead to a substantial reduction in these complications, thereby improving not only short-term outcomes but also long-term prognosis [ 40 42 ]. Moreover, the observed shorter hospital stays in the CPAS group align with studies indicating that enhanced recovery protocols, which include preoperative optimization, can expedite patient recovery and reduce healthcare costs [ 43 , 44 ].…”
Section: Discussionsupporting
confidence: 88%
“…Studies have consistently shown that postoperative complications are associated with decreased long-term survival and increased long-term morbidity [ 34 39 ]. Our findings align with research suggesting that comprehensive preoperative supports can lead to a substantial reduction in these complications, thereby improving not only short-term outcomes but also long-term prognosis [ 40 42 ]. Moreover, the observed shorter hospital stays in the CPAS group align with studies indicating that enhanced recovery protocols, which include preoperative optimization, can expedite patient recovery and reduce healthcare costs [ 43 , 44 ].…”
Section: Discussionsupporting
confidence: 88%
“…A previous study reported similar short-term outcomes according to age but inferior long-term prognosis in older adult patients and those with advanced cancer; therefore, the indications for surgery in older adult patients with advanced cancer require careful consideration. 20 ) Lim et al 4 ) analyzed 1,107 patients who underwent surgery for GC between 2005 and 2009 by classifying them into three age groups (<65, 65–74, and ≥75 years) and observed were more advanced diseases and synchronous cancers in the older groups, suggesting the need for caution before determining the treatment method in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors showed similar results. Komori et al reported that the short-term outcomes after gastrectomy without regard to approach were almost equal between non-elderly and elderly patients [ 26 ]. Mikami et al also showed that there were no differences in short-term outcomes including postoperative morbidity between elderly and non-elderly patients who underwent LG [ 27 ].…”
Section: Discussionmentioning
confidence: 99%